2016
DOI: 10.1016/j.cjtee.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive osteosynthesis of distal tibial fractures using anterolateral locking plate: Evaluation of results and complications

Abstract: PurposeSoft tissue healing is of paramount importance in distal tibial fractures for a successful outcome. There is an increasing trend of using anterolateral plate due to an adequate soft tissue cover on anterolateral distal tibia. The aim of this study was to evaluate the results and complications of minimally invasive anterolateral locking plate in distal tibial fractures.MethodsThis is a retrospective study of 42 patients with distal tibial fractures treated with minimally invasive anterolateral tibial pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…[22][23][24][25] In a study it has been noticed that full range of ankle movements was attained in all the patients (100%) after 6 months (n=38). 26 But another study has shown that full range of ankle movements was achieved in all 26% cases after 6 months (n=19). 27 One more study supported the evidence and also showed that a complete range of ankle movements was attained in all 27% cases after 6 months (n=26).…”
Section: Discussionmentioning
confidence: 93%
“…[22][23][24][25] In a study it has been noticed that full range of ankle movements was attained in all the patients (100%) after 6 months (n=38). 26 But another study has shown that full range of ankle movements was achieved in all 26% cases after 6 months (n=19). 27 One more study supported the evidence and also showed that a complete range of ankle movements was attained in all 27% cases after 6 months (n=26).…”
Section: Discussionmentioning
confidence: 93%
“…Second, lateral malleolus fractures cause local swelling because of the thinner overlying skin and lack of skeletal muscle surrounding the fibula. Extensive soft tissue dissection is needed during the traditional operation to obtain precise fracture reduction and compression (26), which can lead to damage in the limited space and the rigid traditional implants have a high risk of complications such as wound dehiscence and infection, hardware prominence, neurovascular damage, and incision disunion (27,28). Furthermore, incorrect timing of the operation and application of standard large fragment plates have been associated with treatment failure because of steel plate exposure, joint pain or malformation, and even sepsis (25,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Padmanaban kosalaraman et al [22] Devendra Lakhotia et al [23] Present study Wound dehiscence/Superficial infection 16% 12% 2 (10%) Non-union 8% 0 2 (10%) Superficial peroneal nerve neurapraxia 0 1(2%) 1 (5%) Deep infection 0 0 0 Implant failure 4% 0 0…”
Section: Complicationsmentioning
confidence: 96%
“…Mean # union duration Devendra Lakhotia et al [23] 2016 18 Weeks Rohit varma et al [24] 2017 18 weeks Padmanaban kosalaraman et al [23] 2017 21.4 weeks Daniel et al [25] 2016 15 weeks Present study 2017-18 16.9 weeks…”
Section: Year Of Studymentioning
confidence: 99%